The effect of medically-attended injury experience on the use of home safety equipment - Ingyu Jeong; Si Young Jung; Joohyun Suh; Ki Ok Ahn; Jung Ah Bae (Pediatric Emergency Medicine Journal, 2020)
Purpose To assess the effect of medically-attended injury (MAI) on the use of home safety equipment, we analyzed the differences in parents’ perception and attitude about injury prevention, and use of home safety equipment depending on the children’s MAI experiences. Methods From March 2018 through February 2019, we surveyed parents of children aged 5 years or younger via a mobile phone. The parents were divided into the MAI and non-MAI groups. The mobile survey focused on the perception and attitude about injury prevention, and use of home safety equipment (if not used, barriers). Results Of the 204 parents, 75 (36.8%) reported their children’s MAI, comprising the MAI group. This group used the safety equipment more frequently than the non-MAI group (odds ratio, 7.03; 95% confidence interval, 3.39-14.59; P < 0.001). No significant differences between the 2 groups were found in the perception and attitude about injury prevention, barriers to the use of the equipment, and the type of the equipment in use. Conclusion Parents’ experience in their children’s MAIs was associated with the use of home safety equipment, but it did not affect their perception and attitude about injury prevention. A visit to the emergency department with MAI is an opportunity for education on injury prevention and changes of the attitude.